Efek Penggunaan Buku Paket Manual Pembelajaran Seni Budaya Di Kelas VII SMP Negeri 7 Padang - Nela Merianafis; Tulus Handra Kadir (LPPM Politeknik Pratama, 2024)
This research aims to determine the effect of using arts and culture learning manual package books in class VII.1 SMPN 7 Padang. The research method used in this research is a qualitative method because the author did not carry out processing or testing, but the author tried to explore, understand, explain how the arts and culture package book was used at SMPN 7 Padang. Interview questionnaire research instrument for teachers and students. The results of the research on the effect of using a manual package for learning arts and culture in class VII.1 SMPN 7 Padang are that it has an influence on learning arts and culture.